2020
DOI: 10.1111/liv.14631
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis predictability of serum and urine renal markers in patients with decompensated cirrhosis: A multicentre prospective study

Abstract: Background and Aims This prospective observational study aimed to evaluate the best serum and urine markers to assess predictability for the prognosis of patients with decompensated cirrhosis. Methods Serum creatinine and cystatin C (CysC), and urinary N‐acetyl‐beta‐D glucosaminidase (uNAG) and neutrophil gelatinase‐associated lipocalin (uNGAL) levels were measured from hospitalized patients with decompensated cirrhosis. Results In total, 328 patients (mean age, 57.2 ± 12.0 years; 237 men) with decompensated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Conflicting results have been reported regarding the association between tubular markers and the risk of mortality (105,106,119,(139)(140)(141). In a meta-analysis of five studies, increased urine levels of IL-18 and NGAL identified patients at a higher risk of short-term mortality with an AUC of 0.76 (142).…”
Section: Patient Outcomes and Tubular Injury Markersmentioning
confidence: 99%
“…Conflicting results have been reported regarding the association between tubular markers and the risk of mortality (105,106,119,(139)(140)(141). In a meta-analysis of five studies, increased urine levels of IL-18 and NGAL identified patients at a higher risk of short-term mortality with an AUC of 0.76 (142).…”
Section: Patient Outcomes and Tubular Injury Markersmentioning
confidence: 99%
“…However, combination equations of Cr and cystatin C are superior to sCr[ 64 , 65 ]. Cystatin C is an independent predictor of AKI and outcomes, including mortality[ 67 , 68 ]. Other biomarkers of interest include neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), IL-18, and liver-type fatty acid-binding protein (L-FABP)[ 18 , 59 , 69 ].…”
Section: Novel Biomarkersmentioning
confidence: 99%
“…Urinary NGAL predicted poor outcomes in patients as well[ 67 ]. Kim et al [ 68 ] studied urinary NGAL and cystatin C in 328 decompensated cirrhosis patients (41 patients with AKI). The authors found that urinary NGAL is a predictor of AKI and outcomes (including mortality)[ 68 ].…”
Section: Novel Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into novel kidney biomarkers is currently in phases 1-3. A few have had prospective assessment (phase 4; neutrophil gelatinase-associated lipocalin [NGAL], (20) CysC, (21)(22)(23) interleukin 18 [IL18], (24,25) liver-type fatty acid-binding protein [L-FABP], (24,25) kidney injury molecule 1 [KIM-1], (24)(25)(26) β-trace protein (25) ), but application in the fifth phase of biomarker discovery, implementation for decision making, is limited.…”
Section: Role Of Novel Biomarkersmentioning
confidence: 99%